2019
DOI: 10.1113/ep087827
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte and macrophage subtypes as paired cell biomarkers for coronary artery disease

Abstract: New Findings What is the central question of this study?Are circulating monocyte markers correlated with their derived macrophage polarization patterns and coronary artery disease severity? What is the main finding and its importance?There was an inverse relationship between circulating CD16+ monocytes (high) and M2 macrophages (low) that marked coronary disease severity, and the differences in polarization of macrophages were seen despite a week of cell culture ex vivo. This study highlights the importance, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…The differences in polarization of macrophages remained even during one week in a cell culture ex vivo. Furthermore, the authors postulate that circulating monocytes may influence the polarization of lesion macrophages, and that these measures of monocyte and macrophage subtypes may hold potential as new useful biomarkers in cardiovascular disease [43].…”
Section: Essential Mechanisms Promoting Vulnerabilitymentioning
confidence: 99%
“…The differences in polarization of macrophages remained even during one week in a cell culture ex vivo. Furthermore, the authors postulate that circulating monocytes may influence the polarization of lesion macrophages, and that these measures of monocyte and macrophage subtypes may hold potential as new useful biomarkers in cardiovascular disease [43].…”
Section: Essential Mechanisms Promoting Vulnerabilitymentioning
confidence: 99%
“…The results showed that MMP-14 was highly expressed in ox-LDLinduced foamy macrophages, at a level of 5•2-fold higher than that in normal macrophages. To verify the association of MMP-14 expression with in ammatory macrophages, we determined changes in the M1 macrophage markers CD68 and F4/80 [44] and the classical M2 macrophage marker CD206 [45] and con rmed that CD68 and F4/80 expression was signi cantly upregulated and that of CD206 was largely suppressed in ox-LDL-induced macrophages. These trends were reversed by the treatment with the nonselective MMP inhibitor GM6001 [46], which con rmed that MMP-14 could potentially serve as a marker for macrophage in ammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes have also been identified as potential markers of vascular dysfunction and CAD [ 147 , 148 , 149 ]. In patients with CAD, higher monocyte counts were associated with increased risk of cardiovascular events and with peripheral endothelial dysfunction measured by peripheral arterial tonometry [ 147 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Regarding specific monocyte subsets, in a group of CAD patients undergoing coronary artery bypass grafting, endothelial dysfunction was associated with higher expression of activation marker CD11c selectively on CD14+CD16++ monocytes, which were associated with more advanced vascular dysfunction measured as NO-bioavailability and vascular ROS production [ 148 ]. Moreover, in patients undergoing cardiac catheterization, CAD severity was directly associated with CD16+ monocytes and inversely associated with M2 macrophages, suggesting that measures of monocyte and macrophage subtypes could also be potential biomarkers in CAD [ 149 ].…”
Section: Biomarkersmentioning
confidence: 99%